An Examination of Organizational Development at FTIK UIN KH Abdurrahman Wahid Pekalongan From the Viewpoint Of Stakeholders And The Academic Community - Solehudin, Moch. Sugeng; Jaeni, Muhamad; Sopiah, Sopiah; Khobir, Abdul (Jurnal Edusci, 2024)
This study is descriptive qualitative research. From the academic community's and stakeholders' viewpoint, this study identifies the critical areas for developing the Faculty of Tarbiyah and Teacher Training Sciences of K.H. Abdurrahman Wahid State Islamic University Pekalongan. To determine the answers to the issues with organizational development facing the Faculty of Tarbiyah and Teacher Training Sciences at K.H. Abdurrahman Wahid State Islamic University Pekalongan, as seen from the viewpoint of the academic community and stakeholders. In this study, documentation, interviews, and observation are the methods used for gathering data. The academic community and stakeholders of K.H. Abdurrahman Wahid State Islamic University Pekalongan's Faculty of Tarbiyah and Keguruan Sciences are the subjects of this study. The study's findings show that organizational growth inextricably linked to the three pillars of higher education is among the top priorities for FTIK UIN KH Abdurrahman Wahid Pekalongan from the viewpoints of stakeholders and the academic community. In education and learning, research, publications, services, and supporting fields, organizational development refers to the development of research, publications, services, education and learning, and related sectors.